Promoting Inclusion in Nepal: Case Studies of Children with Autism Spectrum Disorder and Down Syndrome in a Classroom Embracing Inclusive Education - Rabindra Shiwakoti; Nisha Pradhananga; Bishna Acharya (Trescode Green Organization, 2025)
This study examined the case studies of children with autism spectrum disorder and down syndrome in an inclusive education classroom. The objectives of this study focus on lived experiences of children with autism spectrum disorder and down syndrome within an inclusive classroom. Drawing on the principles of inclusive education and the unique socio-cultural context of Nepal, the study examines the specific support strategies employed to facilitate their learning and participation. The study has been conducted through qualitative case study of two children, one with autism spectrum disorder and the other with Down syndrome, within an inclusive classroom in Bhaktapur, Nepal. Document review, observation guidelines and interview guidelines were used in this study. Semi-structured interviews were also conducted with teachers and specialists. The collected data is analyzed using thematic analysis, a systematic approach involving several key steps. The themes are reviewed and refined through discussion and comparison with the original data, ensuring they accurately reflect the collected information. This study finds the critical importance of individualized approaches, highlighting how visual supports, structured routines, and sensory regulation strategies significantly benefited the student with ASD. Conversely, the student with Down syndrome thrived in collaborative learning environments, underscoring the value of peer interaction and strengths-based pedagogy. The study emphasizes that successful inclusion in Nepal necessitates ongoing teacher training, collaborative partnerships between educators, families, and therapists, and a sustained commitment to dismantling barriers to create a truly inclusive learning environment where all children can thrive.